La generazione morente. Cosplay zombie come atto di rivendicazione politica - Tirino, Mario (Funes. Journal of narratives and social sciences, 2018)
In September 2013, members of the artistic group “Fin de un Mundo”, disguised as zombies, invaded a Buenos Aires subway station in a demonstrative action against Mauricio Macrì’s austerity policies. On July 6, 2017 about one thousand activists of the “Gestalten” movement invaded the streets of Hamburg, completely covered in white to protest against the de-humanizing effects of technocapitalism. These are just two examples of political use of the zombie figure. The paper aims to explore the evolution of socio-cultural meanings associated with the figure of the zombie in the age of networks and globalization. In this sense, the political claims implemented through acts of zombic cosplay refer to the will of the Millennials to draw attention to the “dying generation”, deprived of horizons and perspectives of life due to the precariousness of work, affections and relationships.